The incidences of postoperative hypoparathyroidism during thyroid surgery with ipsilateral central lymph node dissection for papillary thyroid carcinoma were close to that during thyroid surgery for benign thyroid diseases necessitating surgical intervention: a retrospective study - Wang, Bin; Zhu, Chun-Rong; Fei, Yuan; ShanZhou, Qiyue; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Endocrinology, 2024)
ObjectiveThis study aimed to assess the degree of effect of central lymph node dissection on postoperative hypoparathyroidism incidence.MethodsThe incidence of postoperative hypoparathyroidism was compared between patients receiving thyroidectomy with central neck dissection for papillary thyroid carcinoma and those undergoing thyroidectomy for benign thyroid diseases (thyroid follicular adenoma and/or nodular goiter) necessitating surgical intervention.ResultsThe incidence of postoperative hypoparathyroidism was not significantly different between the groups of lobe thyroidectomy for benign thyroid diseases and lobe thyroidectomy with ipsilateral central lymph node dissection for papillary thyroid carcinoma (immediate: 9.2% vs 3.0%, P = 0.157; protracted: 4.6% vs 0%, P = 0.06; permanent: 0% vs 0%). Similarly, there was no significant difference in the postoperative hypoparathyroidism incidence between total thyroidectomy for benign thyroid diseases and total thyroidectomy with ipsilateral central lymph node dissection for papillary thyroid carcinoma (immediate: 25.0% vs 33.8%, P = 0.12; protracted: 4.5% vs 5.3%, P = 0.99; permanent: 1.1% vs 0.9%, P > 0.99).ConclusionWhile the rates of postoperative hypoparathyroidism during thyroid surgery with ipsilateral central lymph node dissection may be slightly elevated compared to surgery without it for papillary thyroid carcinoma, they remained akin to those observed during surgery for benign thyroid diseases that need surgical management.